Electronic structure and defect density of states of hydrogenated amorphous carbon (a-C:H) as determined by photoelectron and photoelectron yield spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
Amorphous hydrogenated carbon films were prepared by RF-PECVD of CH4 with the self bias varying from 0 to 200V. The films were analysed with x-ray and ultraviolet photoelectron spectroscopy as well as photoelectron yield spectroscopy. The densities as derived from the plasmon energies increase from 1.2 to 1.7 g/cm3 with bias voltage and the sp2/(sp3+sp2) ratio extracted from an analysis of the valence band spectra increases from 15 to 35% over the same range. Two defect bands were identified in the pseudogap, 1.4 eV and 2.4 eV above the π-bonding states with integrated densities that increase from 1·1020 to 7·1020 cm-3 with bias. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.electr_5